Numerical simulation of stress wave propagation in joint rock specimens with cavity defects - Yu, Qun; Yu, Fang; Yao, Dali; Jin, Shengji (Frontiers in Earth Science, 2022)
The process of crack initiation, propagation and coalescence is the essential cause of rock failure. A three-dimensional numerical model based on the microscopic damage mechanics is adopted to simulate the failure process and acoustic emissions (AEs) of jointed rock mass containing a pre-existing hole subjected to stress waves. The numerically simulated results demonstrate that the transmission energy plays an important role in the failure process of specimens. The greater the energy of joint transmission is, the larger the damage of the joint transmission area of the rock mass is. Furthermore, the joint width could significantly influence crack propagation patterns and the damage of the joint transmission area of rock specimens. Moreover, the degree of damage of the local joint transmission area of the rock mass is small but then becomes more obvious when joint angle grows larger. In addition, the wavelength of the stress wave can also affect the failure modes of the rock when stress wave are applied. As the wavelength of the stress wave reduces, the larger the damage of the rock mass is; and the smaller the effect of the joint on crack propagation is. Finally, the numerical results demonstrate that the width of the specimen has a significant effect on its dynamic failure mode and degree, showing an obvious size effect. This finding could explain the lateral growth of an existing flaw in its own plane, which is a phenomenon hat has not been observed in laboratory experiments.